Trends in medical disputes involving anesthesia during July 2009–June 2018: an analysis of the Korean Society of Anesthesiologists database - Ji Won Choi (Korean Journal of Anesthesiology, 2019)
Background To identify trends in injuries and substandard care associated with anesthesia, we analyzed the Korean Society of Anesthesiologists database for anesthesia-related case files from July 2009 to June 2018. Methods Case characteristics, injuries, and outcomes were compared between the first part (July 2009–June 2014, n = 105) and the second part (July 2014–June 2018, n = 92) of the analyzed time period. Results Overall, 132 cases resulted in death. The proportion of fatal cases for sedation was similar to general anesthesia (66.2% vs. 76.3%). The proportion of cases with permanent injury or death decreased significantly in the second part of the period compared with the first part (76.1% vs. 93.3%, P = 0.002). With a growing trend in the proportion of sedation cases, a similar number of sedation and general anesthesia cases were referred during the overall period (77 and 76 cases, respectively). Propofol-based regimens remained the dominant sedation method (89.7% in the first part vs. 78.9% in the second part). The most common adverse event in cases of permanent injury or death was identified as being respiratory in origin (98/182, 53.8%). Permanent injuries or deaths were related to local anesthetic systemic toxicity (LAST) and beach-chair positioning for shoulder surgery, in 8 and 5 cases, respectively. Conclusions Despite the decreasing trend in injury severity with time, several characteristic injury profiles were identified: lack of vigilance in propofol-based sedation, neurological injuries related to the beach-chair position, and LAST occurring during tumescent anesthesia or brachial plexus block.